Enhanced Bug Localization through Version Tag Embedding: A Comprehensive Approach to Efficient Software Development - Rao, N. Rama; Suresh, K. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In order to localize bugs, this study suggests putting version markers in software delivery files. The article focuses on the importance and method of the planned build process, in which developers upgrade internal version numbers prior to registration to aid with precise problem localization. It is suggested that version tagging automation be used as a workable solution to problems like identifying file sources and exploiting vulnerabilities. The suggested solution has advantages in better managing project complexity, protecting against software infiltration, lowering costs, improving quality, and boosting productivity and dependability. The use of date tagging and external release numbers for software identification and compatibility testing is also covered in the article. Operating systems, version control, build tools, web servers, application servers, scripting languages, bug tracking tools, databases, and programming languages are all used in the research's specialised testing and development environment. The branching, merging, check-out, check-in, parameters, build numbering approach, and tagging operations are all thoroughly detailed. The suggested approach shows how to embed and update internal version tags in deliverable files, improving traceability and facilitating problem fixes throughout the build process. Discussions of the approach's importance in terms of bug detection and eradication, release management, complexity handling, intrusion defence, cost savings, and dependability are included. The page includes graphs that show the number of builds and the link between the number of builds and the state of problems that have been discovered and repaired before and after releases. Overall, the research offers workable solutions for effective software development and problem management by presenting a unique bug localization technique employing version tagging.